A Comparative Performance Evaluation of Extended AANF with Different Parameter Estimation Techniques for Renewable Energy Integration. Issue 17 (21st October 2017) - Shitole, Amardeep B.; Suryawanshi, Hiralal M.; Sathyan, Shelas; Talapur, Girish G.; Ballal, Makarand S.
Abstract: This paper presents real time performance evaluation of three phase extension of an amplitude adaptive notch filter (AANF) for online estimation of frequency, amplitude, and sequence components of the input grid voltage signal. The performance of an extended AANF is compared with conventional synchronous reference frame-phase lock loop (SRF-PLL), enhanced phase lock loop (EPLL), and existing adaptive notch filter (ANF). Comparative analysis has been carried out based on their ability in extracting frequency and amplitude of input grid voltage signal under balanced and unbalanced voltage sag/swell, frequency shift and distorted grid condition. Three phase AANF method provides high degree of accuracy than SRF-PLL, EPLL, and ANF in extracting appropriate signal information for unbalanced and harmonically distorted grid condition. The important feature of this method is its amplitude adaptability, which improves its speed of response and accuracy when grid signal is of variable amplitude. OPAL-RT's (OP4500) real time controller with an in-built Xilinx Kintex-7 FPGA processor is used for real time implementation. Experimental results validate fast and accurate performance of an extended AANF in extracting frequency, amplitude, and sequence components of the utility grid voltage signal, which can be further used for performance improvement of grid connected renewable energy systems, custom power devices, and flexible ac transmission systems (FACTS) devices.